Exercise training increases skeletal muscle mitochondrial volume density by enlargement of existing mitochondria and not de novo biogenesis. (6th July 2017) - Meinild Lundby, A.‐K.; Jacobs, R. A.; Gehrig, S.; de Leur, J.; Hauser, M.; Bonne, T. C.; Flück, D.; Dandanell, S.; Kirk, N.; Kaech, A.; Ziegler, U.; Larsen, S.; et al.
Abstract: Aims: (i) To determine whether exercise‐induced increases in muscle mitochondrial volume density (MitoVD ) are related to enlargement of existing mitochondria or de novo biogenesis and (ii) to establish whether measures of mitochondrial‐specific enzymatic activities are valid biomarkers for exercise‐induced increases in MitoVD . Method: Skeletal muscle samples were collected from 21 healthy males prior to and following 6 weeks of endurance training. Transmission electron microscopy was used for the estimation of mitochondrial densities and profiles. Biochemical assays, western blotting and high‐resolution respirometry were applied to detect changes in specific mitochondrial functions. Result: MitoVD increased with 55 ± 9% ( P < 0.001), whereas the number of mitochondrial profiles per area of skeletal muscle remained unchanged following training. Citrate synthase activity (CS) increased (44 ± 12%, P < 0.001); however, there were no functional changes in oxidative phosphorylation capacity (OXPHOS, CI+II P ) or cytochrome c oxidase (COX) activity. Correlations were found between MitoVD and CS ( P = 0.01; r = 0.58), OXPHOS, CI+CIIP ( P = 0.01; R = 0.58) and COX ( P = 0.02; R = 0.52) before training; after training, a correlation was found between MitoVD and CS activity only ( P = 0.04; R = 0.49). Intrinsic respiratory capacities decreased ( P < 0.05) with training when respiration was normalized to MitoVD. This was not the case when normalized to CS activity although the percentage change was comparable. Conclusions: MitoVD was increased by inducing mitochondrial enlargement rather than de novo biogenesis. CS activity may be appropriate to track training‐induced changes in MitoVD.